Закономерности сополимеризации стирола и бутилметакрилата - Бондалетов О. В. Олег Владимирович; Бондалетова Л. И. Людмила Ивановна; Сутягин В. М. Владимир Михайлович; Бондалетов В. Г. Владимир Григорьевич; Таванова М. Э.; Кустова Е. А. (2010, 2010)
Заглавие с экрана